P168 The outcome and complications of endoscopic ultrasound-guided drainage in pancreatic fluid collections. (19th June 2022) - Javed, Farwah; Hassan, Ghias ul; Rasool, Shafqat; Nasir, Bilal; Haque Toor, Israr Ul; Nawaz, Faisal; Tayyab, Ghias; Dilshad, Akif; Amjad, Ibtesaam
Abstract : Introduction: The term PFCs comprise of acute fluid collections (<4 weeks after onset ) i.e Acute peripancreatic fluid collection(APFC) and Acute necrotic collection(ANC) and chronic collections (>4 weeks after onset) i.e pancreatic pseudocysts and walled-off pancreatic necrosis(WOPN) . Symptomatic PFCs require drainage either through surgical, percutaneous, or endoscopic approaches. Endoscopic ultrasound- guided and surgical drainages both have comparable success rates, 89%–100% and 82%–100% respectively, but EUS- guided approach has several advantages including lower costs, decreased hospital stay and lower mortality. An endoscopic ultrasound-guided approach using a Seldinger technique is usually preferred. Methods: This retrospective case series was conducted in Gastroenterology division of Medical unit 1, Lahore General Hospital on the patients with symptomatic PFC who presented over a period of two years, between January 2019 and December 2020. Records were analyzed for demographic data, indications for the procedure, characteristics of PFCs, complications and success related to EUS guided drainage. Statistical analyses were performed using the SPSS Version 24. Results: Total number of patients was 80 with a mean age 44 with range of 16-65 . Technical success was achieved in 78(97.5%) and clinical success in 77/78(98.7%) of patients. Major complications requiring intervention were 11(13.7%). There were 6(7.5%) recurrences and no procedure related mortality Conclusions: Transgastric EUS guided drainage is an effective minimally invasive procedure for the management of PFCs and is also effective for management of WOPN. Good clinical outcomes, reduced procedure cost with low complication rates makes it first line option for the management of PFCs